REAL-TIME FINANCIAL REPORTING: THE CHALLENGES AND BENEFITS OF CLOUD-BASED ACCOUNTING SYSTEMS - Nurhaini Nurhaini; Lucas Lima; Raul Gomez (Yayasan Adra Karima Hubbi, 2026)
Rapid digital transformation has fundamentally reshaped financial reporting by increasing organizational demand for timely, accurate, and transparent financial information. Conventional accounting systems frequently struggle to satisfy these expectations because periodic reporting, fragmented data management, and limited accessibility reduce organizational responsiveness and decision quality. This study aimed to evaluate the benefits and challenges of cloud-based accounting systems in supporting real-time financial reporting and organizational performance. A mixed-methods sequential explanatory design was employed using data collected from 310 organizations and 1,240 accounting professionals representing multiple industrial sectors. Quantitative analyses incorporated descriptive statistics, structural equation modeling, hierarchical regression, mediation and moderation analyses, while qualitative evidence from expert interviews, organizational observations, and policy document reviews was analyzed through thematic analysis. Findings demonstrated that cloud-based accounting significantly improved reporting timeliness, financial reporting accuracy, audit efficiency, managerial decision-making, organizational agility, and regulatory compliance. Reporting timeliness partially mediated the relationship between cloud capability and organizational performance, whereas cybersecurity readiness and employee digital competence strengthened implementation effectiveness.